ANALISIS DAYA SERAP TENAGA KERJA LULUSAN SEKOLAH MENEGAH KEJURUAN BIDANG KEAHLIAN TATA BUSANA DI KOTA MAKASSAR - Andi Ahlia Fachriani; Aisyah Hading; Hasanah Nur (Program Studi S2 Pendidikan Teknologi dan Kejuruan, 2021)
This study is a survey research that aims to determine the extent of absorption graduates of vocational areas of expertise of fashion in DU / DI clothing and relevance of soft skills and hard skills of labor graduates of vocational expertise of fashion with the needs of the DU / DI clothing in the city of Makassar in employment . The population in this study were all DU/DI workers in the field of fashion in Makassar City, totaling 406 workers. The sampling technique used in this study was purposive sampling, namely sampling based on certain criteria consisting of 43 respondents from 15 DU/DI in the field of fashion. Data collection techniques in this study used questionnaires and interviews obtained through primary data and secondary data. The analysis in this study uses descriptive analysis and percentage calculations. The results showed that the level of absorption of Vocational High School graduates in the Fashion Designfashionin Makassar City was still in the very low category, namely 11% or 43 of the 406 workers absorbed in the fashionExpertise in theindustryindustry . fashion is in the category is as high as 81%, hardskill labordressmaking vocational graduates are in very high category by 39%.